Exploring general practitioners' views and experiences on suicide risk assessment and management of young people in primary care: a qualitative study in the UK. Issue 1 (12th January 2016) - Michail, Maria; Tait, Lynda
Abstract : Objective: To explore general practitioner (GP) views and experiences of assessing, communicating with and managing suicidal young people with the aim of co-producing an educational intervention on youth suicide prevention tailored to GPs' perceived needs. Design: Qualitative focus group study using framework analysis. Setting: 5 inner city general practices in Nottingham. Participants: 28 GPs took part (9 males) with mean age of 37 years. The median number of years of professional experience was 13. Participants were recruited through convenience sampling based on accessibility, interest in the study and willingness to participate. Results: 3 themes emerged from the data in relation to GP's attitudes and beliefs towards suicide; the challenges GPs experience when it comes to the assessment and management of suicide risk in young people; and optimal ways of addressing some of these challenges through the provision of specialist education and training targeting GPs' knowledge and clinical skills in this field. Conclusions: The findings revealed wide variations in the understanding and operationalisation of risk among GPs, which has subsequent implications to how GPs perceive risk should be assessed. GP education on suicide risk assessment and management in youth should promote a holistic understanding and assessment of risk and its individual, social and contextual influences.